Family communication and bi-dimensional student mental health in adolescents: A serial mediation through digital game addiction and school belongingness - Deniz, M. Engin; Kurtulus, Hacer Yildirim; Kaya, Yagmur (WILEY, 2024)
The presence of communication within the family can be considered as a protective factor in preventing the development of mental health problems in school by acting as a buffer against mental health problems in adolescents. Thus, this study, which was designed to reveal the potential mechanisms between family communication and bi-dimensional student mental health (psychological well-being/distress) in Turkish adolescents, examined the serial mediator role of digital game addiction and school belongingness. The study sample consists of a total of 397 volunteering Turkish adolescents, including 206 girls (51.9%) and 191 boys (48.1%). The participants' ages range from 14 to 17 (M = 14.63 years, SD = 0.60). In this study, a cross-sectional and explanatory design based on structural equation modeling was used. The main findings of the study are as follows: (1) digital game addiction mediated the relationship between family communication and psychological well-being/distress, (2) school belongingness mediated the relationship between family communication and psychological well-being/distress, and (3) the relationship between family communication and psychological well-being/distress was serially mediated by both digital game addiction and school belongingness. Digital game addiction mediated the relationship between family communication and psychological well-being/distress. School belongingness mediated the relationship between family communication and psychological well-being/distress. Both digital game addiction and school belongingness serially mediated the relationship between family communication and psychological well-being/distress.
Keywords: digital game addiction; family communication; psychological distress; psychological well-being; school belongingness; student mental health; PROBLEMATIC INTERNET; CHILDREN; VALIDATION; HAPPINESS; DISTRESS; FACEBOOK; PARENT; SCALE; Psychology